Strategi Public Relations dalam Membangun Citra Lembaga Pendidikan: Pendekatan Terintegrasi Konvensional dan Digital - Rosliani, Lia; Prihatini, Firda; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes Public Relations strategies in building organizational image through a Systematic Literature Review (SLR) approach. The background of the study is the importance of organizational image to increase public trust and competitiveness amidst the development of communication technology. Data were collected from 30 relevant scientific articles (20 national journals and 10 international journals), and analyzed using content analysis through the stages of identification, classification, comparison, and synthesis. The results show that Public Relations strategies include media relations, event organizing, communication with stakeholders, and strengthening organizational branding, accompanied by a shift from conventional Public Relations to Digital Public Relations that utilizes social media and digital technology. The study concludes that an effective Public Relations strategy is integrated, combining conventional and digital communication systematically. The novelty of the study lies in the development of the concept of an integrated Public Relations strategy to build an organizational image in a comprehensive and sustainable manner.